PROFITABILITY, LEVERAGE, CARBON EMISSION DISCLOSURE: THE MODERATING ROLE OF PROFIT GROWTH - Santoso, Agnes Novita Mega Putri; Rakasiwi, Devina Aurellia; Rachmadhika, Hendra Arie; Firmansyah, Amrie (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This research examines the relationship between leverage, profitability, and carbon disclosure in the Indonesia Stock Exchange (IDX) energy industry from 2019 to 2022. As a moderator, this study also examines how profit growth affects the relationship between the three variables. Panel data multiple linear regression analysis served as the method of hypothesis testing. This study analyzes data on energy sector businesses listed on the Indonesia Stock Exchange during 2019–2022, totaling 84 observation periods. The results showed how profitability and leverage significantly negatively impacted carbon disclosure. Profit growth highlights how negatively profitability affects carbon disclosure. However, the relationship between leverage and carbon emission disclosure remains despite revenue increases. The findings provide important insights into the disclosure practices of the energy sector concerning carbon emissions and their impact on environmental sustainability. Based on the study's findings, businesses and pertinent parties should be able to develop policies that support the transition to a more sustainable energy industry.